DAMPAK KRISIS EKONOMI TERHADAP KINERJA EKONOMI NASIONAL DAN KEMISKINAN (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2012)
The purpose of this research was to analyze Indonesian economic performance after global economic crisis in 2008. Beside that, the purpose of this research was to analyze the relationship between global ecomic crisis and poverty. Basic concept of this research used Kuznets’s Theory (1971). This theory explain that at the begining of development process, rate of poverty tend to rise and at the ending of development process, rate of poverty tend to decline. This research used descriptive-quantitative analysis and based on data of Badan Pusat Statistik (BPS). Gini Ratio was used as indicator of size discrepency of community’s income. The result of this research indicated that after economic crisis in 1997, Indonesian economic had negative growth 13,24%. Beside that, the size of poverty community had slight increase from 21,5 billion persons in 1996, become 79,4 billion persons in 1998. After economic crisis in 2008, economic growth had decline, even at 2010 economic growth had good condition with growth as 7,1%. Unfortunately, good condition of economic growth did not followed by dissemination of national income. It was proved by Ratio Gini from 0,345 in 2006, become 0,39 in 2010. This indicated that discrepency of economic tend to rise.